Human-on-Chip Technology: Current State and Future Challenges - Kumar, Santosh; Dagli, Namrata; Haque, Mainul (Bangladesh Journal of Medical Science, 2024)
Abstract not available Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 7-11